2001
DOI: 10.1073/pnas.221467198
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast folding of WW domains without structured aromatic clusters in the denatured state

Abstract: Ultrafast-folding proteins are important for combining experiment and simulation to give complete descriptions of folding pathways. The WW domain family comprises small proteins with a threestranded antiparallel ␤-sheet topology. Previous studies on the 57-residue YAP 65 WW domain indicate the presence of residual structure in the chemically denatured state. Here we analyze three minimal core WW domains of 38 -44 residues. There was little spectroscopic or thermodynamic evidence for residual structure in eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
121
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(140 citation statements)
references
References 34 publications
17
121
2
Order By: Relevance
“…To combat slippage in this functionally important region, Nature has used two strategies: fast folding in the remainder of the protein, and a surface-exposed hydrophobic pair. The kinetic phase corresponding to the folding of the remainder of the protein was reported to be the fastest known folding protein to date (18), which suggests evolutionary pressure to form the scaffold for loop 2 quickly, which in turn helps promote correct formation of this loop. The surface-exposed hydrophobic pair, meanwhile, provides a reward for correctly registering the strands, reducing slippage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To combat slippage in this functionally important region, Nature has used two strategies: fast folding in the remainder of the protein, and a surface-exposed hydrophobic pair. The kinetic phase corresponding to the folding of the remainder of the protein was reported to be the fastest known folding protein to date (18), which suggests evolutionary pressure to form the scaffold for loop 2 quickly, which in turn helps promote correct formation of this loop. The surface-exposed hydrophobic pair, meanwhile, provides a reward for correctly registering the strands, reducing slippage.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the thermodynamics and kinetics of folding were compared between the following three WW domains (18): one from hYAP, one from murine forminbinding protein (FBP) 28, and a de novo-designed WW domain. All three of the aforementioned studies (16)(17)(18) reported singleexponential kinetics for folding, corresponding to an apparent two-state mechanism.…”
mentioning
confidence: 99%
“…β-sheet formation. It should be noted that the WW domains have been the subject of extensive theoretical (1,14,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and experimental (15)(16)(17)(29)(30)(31)(32)(33)(34)) studies because of their small size, biological importance (35), and interesting fast-folding kinetics.…”
Section: Significancementioning
confidence: 99%
“…1N), has been shown to fold with biphasic kinetics exhibiting intermediates during folding (3,5,6,(11)(12)(13)(14)(15)(16). We address this problem here with the design of new FBP28 WW domain mutants and by examining their structural properties and folding kinetics.Because of the small size, fast folding kinetics, and biological importance, the formation of intermolecular β-sheets is thought to be a crucial event in the initiation and propagation of amyloid diseases, such as Alzheimer's disease, and spongiform encephalopathy, FBP28, and other WW domain proteins (e.g., Pin1 and FiP35) have been the subjects of extensive experimental (4,11,(17)(18)(19)(20)(21)(22)(23) and theoretical (3,5,6,(12)(13)(14)(15)(16)(24)(25)(26)(27) studies. However, a folding mechanism of the FBP28 was debatable for a long time because of its complexity.…”
mentioning
confidence: 99%